POTENSI FITO-BIOFILM DALAM PENURUNAN KADAR BOD DAN COD PADA LIMBAH DOMESTIK DENGAN TANAMAN KANGKUNG AIR (Ipomoea aquatica) MEDIA BIOFILTER SARANG TAWON (Studi kasus: Perumahan Graha Mukti, Tlogosari Semarang) - Dewi Fitria Marlisa (Jurnal Teknik Lingkungan, 2012)
Domestic activities such as household (residential) result in a waste water effluent. Domestic wastewater is one of the biggest polluters of water sources. High content of organic material in domestic sewage pollution on the bodies of water increases the receiver. One indication of water contamination levels of BOD and COD is in excess of standard quality. One effective method that can be taken into consideration is the Phyto-biofilm technique to reduce levels of BOD and COD are appropriate quality standards. Fito-biofilm technology is a combination of waste water treatment using water spinach plants and biofilms formed by the honeycomb media. The study was conducted by using Phyto-biofilm reactor with a system plug flow. Based on the results of this study, found that the domestic wastewater treatment with Phyto-biofilm technique is able to lower the BOD parameter of 97% and COD 95%.